Preexercise medium-chain triglyceride ingestion does not alter muscle glycogen use during exercise - Horowitz, J. F.; Mora-Rodriguez, R.; Byerley, L. O.; Coyle, E. F. (Journal of Applied Physiology, 2000)
This investigation determined whether ingestion of a tolerable amount of medium-chain triglycerides (MCT; ~25 g) reduces the rate of muscle glycogen use during high-intensity exercise. On two occasions, seven well-trained men cycled for 30 min at 84% maximal O2 uptake. Exactly 1 h before exercise, they ingested either 1) carbohydrate (CHO; 0.72 g sucrose/kg) or 2) MCT+CHO [0.36 g tricaprin (C10:0)/kg plus 0.72 g sucrose/kg]. The change in glycogen concentration was measured in biopsies taken from the vastus lateralis before and after exercise. Additionally, glycogen oxidation was calculated as the difference between total carbohydrate oxidation and the rate of glucose disappearance from plasma (Rd glucose), as measured by stable isotope dilution techniques. The change in muscle glycogen concentration was not different during MCT+CHO and CHO (42.0 ± 4.6 vs. 38.8 ± 4.0 µmol glucosyl units/g wet wt). Furthermore, calculated glycogen oxidation was also similar (331 ± 18 vs. 329 ± 15µmol · kg1 · min1). The coingestion of MCT+CHO did increase (P < 0.05) Rd glucose at rest compared with CHO (26.9 ± 1.5 vs. 20.7 ± 0.7 µmol ·kg1 · min1), yet during exercise Rd glucose was not different during the two trials. Therefore, the addition of a small amount of MCT to a preexercise CHO meal did not reduce muscle glycogen oxidation during high-intensity exercise, but it did increase glucose uptake at rest.